Improvement of powder management and recycling in laser sintering - Wan Yusoff, Wan Ahmad Yusmawiza; Pham, Duc Trung; Dotchev, Krassimir (2011)
Nowadays the utilisation of PA12 powders using the Laser Sintering (LS) process has become very popular, not only for rapid prototyping but also for the direct manufacturing of bespoke parts. In order to fabricate parts with good quality and to avoid the “orange peel” occurrence, the users of LS machines apply a constant refresh rate with a higher portion of new powder. As a result, a huge amount of recycled powder has to be discarded. This paper reports on an experimental study of the deterioration of PA12 powder properties in the LS process. The main aim of this research is to develop a methodology for powder recycling and for controlling the input material properties that will ensure a good and consistent quality of the fabricated parts and a more efficient use of the LS material